A Note on Merger and Acquisition Evaluation - Benjamin Furlan; Harald Oberhofer; Hannes Winner (Austrian Institute of Economic Research (WIFO), 2014)
This note proposes the continuous treatment approach as a valuable alternative to propensity score matching for evaluating economic effects of mergers and acquisitions (M&As). This framework allows to consider the variation in treatment intensities explicitly, and it does not call for the definition of cut-off values in traded ownership shares in order to construct a binary treatment indicator. We demonstrate the usefulness of this approach using data from European M&As and by relying on the example of post-M&A employment effects.
Keywords: 330; Merger and acquisition evaluation; continuous treatment models; generalised propensity score matching; employment effects